2017
DOI: 10.1080/09712119.2017.1333435
|View full text |Cite
|
Sign up to set email alerts
|

Histological, cytogenetic and endocrine evaluation in twenty-five unilateral cryptorchid horses

Abstract: Data from 49 horses (25 unilateral cryptorchid and 24 as control group) are reported to determine macroscopic and microscopic characteristics of the testes, as well as to characterize their karyotype and hormonal levels. Histology showed that only Sertoli cells were found in the lumen of the seminiferous tubules of the cryptorchid testes, while spermatogenesis in the scrotal testes resulted normal. Cytogenetic evaluation showed that all cryptorchid horses were normal males (2n = 64, XY). In addition, the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These changes are more pronounced in abdominal than in inguinal testes. 56,59,60 Severe testicular compromise following torsion of the spermatic cord may lead ischemia, 59,61,62 tissue necrosis and atrophy, which may sometimes be confused with true monorchidism, a much less common condition. [63][64][65][66][67] Histochemical studies of cryptorchid testes revealed a disruption of the morphology and histochemistry of both Leydig and Sertoli cells.…”
Section: Histopathology Of Retained Testismentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are more pronounced in abdominal than in inguinal testes. 56,59,60 Severe testicular compromise following torsion of the spermatic cord may lead ischemia, 59,61,62 tissue necrosis and atrophy, which may sometimes be confused with true monorchidism, a much less common condition. [63][64][65][66][67] Histochemical studies of cryptorchid testes revealed a disruption of the morphology and histochemistry of both Leydig and Sertoli cells.…”
Section: Histopathology Of Retained Testismentioning
confidence: 99%
“…Other neoplasms reported in undescended testes including carcinomas, 53 interstitial cell tumors, 71,84 malignant Sertoli cells tumors, 85 and leiomyosarcoma. 86 Horses with abdominal retention of a testis may sometimes present with an acute abdomen (colic) due to torsion of the spermatic cord 61 or jejunal entrapment and strangulation. 73,87…”
Section: Histopathology Of Retained Testismentioning
confidence: 99%
“…The blood samples destined for chromosomical and cytogenetic analyses were collected in both 10 mL tubes without anticoagulant and lithium-heparinized tubes, placed in a container at a temperature of 5 • C, and sent to the cytogenetics laboratory of the Department of Veterinary Medicine and Animal Production of the Federico II University of Naples. The concentration of serum testosterone (T) was determined using a solid-phase I125 radioimmunoassay (Coat-A-Count Testosterone ® , Siemens, Camberley, UK), as described by Vilar et al [36]. The assay sensitivity was of 0.05 ng/mL, and the interassay coefficient of variation was 13.9%.…”
Section: Hormonal Analysismentioning
confidence: 99%
“…Incidence of perioperative and postoperative complications ranged from 10.0-60.0% according to surgical procedure or postoperative management [5][6][7][8][9][10][11]. Indwelling testis in the abdomen of cryptorchid equids can still produce testosterone [12], which may contribute to unwanted behavior. Laparotomy or laparoscopic surgery must be performed to remove the testis from cryptorchid animals.…”
Section: Introductionmentioning
confidence: 99%